Development of therapeutic digestive endoscopy robots: a narrative review - Yaxian Kuai; Jing Li; Zhaoyi Chen; Bin Sun; Xu Wang; Derun Kong (Videosurgery and Other Miniinvasive Techniques)
Introduction: With the continuous development of science and technology, robotics technology has gradually penetrated into various fields of application. In medicine, it is widely used in surgery to improve procedural accuracy and patient safety.